Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pengrajin Mebel Dikecamatan Tamansari Kota Tasikmalaya (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Furniture business units in the city of Tasikmalaya altogether had 217 business units in 2018 with an investment value of IDR 28,677,699,000, a production value of IDR 82,656,245,000 and absorbing a workforce of 1,538 people. The aim of this research is to gain a better understanding of the use of raw materials, capital and labor by furniture craftsmen in Tamansari District, Tasikmalaya City. The analytical tools used in this research are multiple regression, coefficient of determination, and hypothesis testing. Multiple regression is used to identify the relationship between independent variables (raw materials, capital, labor) and dependent variables (income of furniture craftsmen). The research results show that raw materials, working capital and labor have a significant influence on the income of furniture craftsmen in Tamansari District, Tasikmalaya City. This means that efficient use of raw materials, capital and labor can increase the income of furniture craftsmen in the region. These results can be used as a basis for developing and improving the business of furniture craftsmen in Tasikmalaya City